Promoting EFL students’ critical thinking and self-voicing through CIRC technique in Academic Writing courses - Andi Susilo; Restu Mufanti; Aris Fitriani (Studies in English Language and Education, 2021)
Critical thinking and self-voicing are two demanding skills that facilitate students to produce concise, authorial academic texts. While most writing programs and research have paid much attention to improving students’ writing achievement, less attention is given to promote these two skills in English as a Foreign Language (EFL) writing classrooms. This article reports a classroom-based study investigating the use of the Cooperative Integrated Reading and Composition (CIRC) technique to promote EFL students’ academic writing skills. It particularly examines how the CIRC technique helps to foster students’ critical and self-voicing stance in developing argumentative texts. A participatory qualitative study was employed, involving 64 undergraduate students majoring in English Education. Data were generated from the participants’ writing portfolios, observations, and the teacher’s reflections. The collected data were managed, classified, and analyzed using NVivo 12 to elicit the emerging themes. Drawing on the qualitative content analysis, the results showed that the CIRC technique helped to shape the participants’ critical thinking and self-voicing skills which were consistently demonstrated during the student-centered activities and their writing results. The participants could engage in productive writing processes, such as critical reading, note-taking, summarizing, drafting and revising composition, peer-reviewing, and other related collaborative skills. The findings indicated that the development of students’ critical thinking and self-voicing skills simultaneously affected the quality of their academic writing texts.